2015
DOI: 10.1080/17461391.2015.1046192
|View full text |Cite
|
Sign up to set email alerts
|

Contact technique and concussions in the South African under‐18 Coca‐Cola Craven Week Rugby tournament

Abstract: In rugby union, understanding the techniques and events leading to concussions is important because of the nature of the injury and the severity and potential long-term consequences, particularly in junior players. Proper contact technique is a prerequisite for successful participation in rugby and is a major factor associated with injury. However, the execution of proper contact technique and its relationship to injury has yet to be studied in matches. Therefore, the aim of this study was to compare contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 32 publications
1
70
1
Order By: Relevance
“…Indeed, the reality is that at some age, tackling will be part of Rugby Union, and it is true that this aspect of the sport is most injurious, accounting for between 50% and 70% of injuries in all forms of the game 15 38 39. It has also been documented that poor or inappropriate tackle technique is more likely to be observed in tackles leading to head injuries40 and all contact injuries41 in high-level Under-18 players. Furthermore, McIntosh et al 42 found that younger (Under-15) players more often used a passive shoulder tackle, whereas older players used an active shoulder tackle more frequently.…”
Section: Reducing Risk In Rugby Union: Unknown Variables and Potentiamentioning
confidence: 99%
“…Indeed, the reality is that at some age, tackling will be part of Rugby Union, and it is true that this aspect of the sport is most injurious, accounting for between 50% and 70% of injuries in all forms of the game 15 38 39. It has also been documented that poor or inappropriate tackle technique is more likely to be observed in tackles leading to head injuries40 and all contact injuries41 in high-level Under-18 players. Furthermore, McIntosh et al 42 found that younger (Under-15) players more often used a passive shoulder tackle, whereas older players used an active shoulder tackle more frequently.…”
Section: Reducing Risk In Rugby Union: Unknown Variables and Potentiamentioning
confidence: 99%
“…They analysed a total of 6618 tackle events, of which 81 resulted in injury, and found no statistical evidence of any difference in the odds of receiving an injury during an active shoulder tackle compared with any one of passive shoulder tackle, jersey tackle, ankle tap or smother (p>0.05 for each); the only association with technique was an increased risk of injury when a player was tackled by two players simultaneously as opposed to being tackled by a single tackler 51. Tucker et al cite a small study by Hendricks et al which found weak evidence of an association between tackler proficiency and likelihood of concussion 49. Burger et al did find evidence that improved tackle technique on the part of both the ball carrier and the tackler was associated with reduced risk of injury 48.…”
Section: Introductionmentioning
confidence: 98%
“…Given the growing concern over head injuries in sport, a focus on the characteristics of tackles that expose players to the highest risk of head injury is warranted. To our knowledge, no large-scale video analysis study has investigated specific risk factors for head injuries during tackles in professional rugby union, although similar studies exist for Rugby League,8 Australian football9 and American football,10 with smaller studies in rugby union 11…”
Section: Introductionmentioning
confidence: 99%